The associations between reading mind in the eyes abilities, alexithymia, empathy, and bullying behavior in Turkish adolescents - Sen Demirdogen, Ezgi; Aluc, Nursah; Akdeniz, Burak; Basar, Dusum; Warikoo, Nishchint; Yavuz, Mesut (WILEY, 2022)
Problem: The development of any program to reduce bullying is possible with a better understanding of the associated underlying factors with its emergence. This study, therefore, aimed to investigate three different social cognitive abilities: abilities to read minds in the eyes, alexithymic personality traits, and empathy, in association with bullying behaviors in adolescents. Although these factors have been studied separately, our data highlighted their effect, relationship, and interconnectivity. Methods: The participants consisted of 351 adolescents (57.8% girls) aged 13-16 years (mean: 14.32 +/- 0.73 for girls, 14.38 +/- 0.86 for boys). The data used in this cross-sectional study were collected using self-reported questionnaires. Pearson's moment product correlation analysis and hierarchical linear regression analysis were performed to evaluate the associations between variables. Findings: Bullying behavior levels were higher in male adolescents compared with females. The results indicated that bullying behavior was associated with low levels of reading minds in the eyes abilities, alexithymic personality traits, and low affective empathy levels. Conclusion: These findings highlight the critical impact of the poor comprehension of mental states and emotional statuses of other people and low emphatic thinking capacity in the emergence of bullying behaviors among adolescents. Therapeutic interventions focusing on improving these factors may therefore be useful in prevention and management programs for bullying behavior.
Keywords: adolescence; alexithymia; bullying; empathy; reading minds in the eyes; INDIVIDUAL-DIFFERENCES; EMOTION DYSREGULATION; GENDER-DIFFERENCES; INVOLVEMENT; SCHOOL; VICTIMIZATION; AGGRESSION; CHILDREN; STUDENTS; BULLIES; Nursing